Democratic Republic of Timor-Leste : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
The staff report for the 2004 Article IV Consultation on the Democratic Republic of Timor-Leste highlights economic developments and policies. Progress has been made in consolidating the new government's administrative power and fostering a stable political environment, despite some early challenges. Despite progress in economic reconstruction, significant economic challenges remain. These challenges center on the strengthening of medium-term growth prospects to alleviate widespread poverty. Given the constraints of the current regime, prudent fiscal and wage policies will be essential to help avoid attrition in Timor-Leste's external competitiveness.